2015
DOI: 10.1186/s12889-015-2036-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Swedish physical activity on prescription model on health-related quality of life in overweight older adults: a randomised controlled trial

Abstract: BackgroundThe effects of physical activity on prescription (PAP) on health-related quality of life (HRQoL) in overweight adults are unclear. We therefore aimed to explore the effects of the Swedish PAP model on HRQoL in overweight older adults.MethodsParticipants were recruited from a cohort of men and women born between 1937 and 1938, and living in Stockholm County. Inclusion criteria were; insufficiently physically active, i.e. <30 min of at least moderate intensity physical activity (PA) per day; body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 40 publications
1
46
2
3
Order By: Relevance
“…Moreover, adults with multiple chronic illnesses appeared to receive similar benefit from recommended levels of PA. These results are consistent with randomized controlled trials that have shown increases in PA with simultaneous increases in HRQOL [19,20,21,22]. These findings are further supported by studies that have shown increased HRQOL in physically active participants with chronic diseases [23][24][25][26][27][28][29].…”
Section: Odds Ratios (Ors)supporting
confidence: 80%
“…Moreover, adults with multiple chronic illnesses appeared to receive similar benefit from recommended levels of PA. These results are consistent with randomized controlled trials that have shown increases in PA with simultaneous increases in HRQOL [19,20,21,22]. These findings are further supported by studies that have shown increased HRQOL in physically active participants with chronic diseases [23][24][25][26][27][28][29].…”
Section: Odds Ratios (Ors)supporting
confidence: 80%
“…As we know, mental health disorders are major contributors to the global burden of disease and their inverse relationship with physical activity is widely accepted [28] [29]. In Sweden, Olsson et al [30] found a significant effect of physical activity on prescriptions during a 6-month intervention and significantly improved health-related QoL in overweight adults. Even in a study of very elderly (85-year-olds), significant associations were found between QoL and physical fitness [31].…”
Section: Discussionmentioning
confidence: 99%
“…listening to the patient's perspective, offering specific encouragement) were well aligned with those advocated for fostering autonomous motivation in exercise settings 46,51 . Such communication strategies share similarities with motivational interviewing 52 , which has been shown to be effective when implemented as part of an ERS 53 . Therefore upskilling referring HPs and family members in MI techniques (e.g.…”
Section: Interpersonal Levelmentioning
confidence: 99%